Topik dan Metode Pencarian Sumber Pada Laporan Evidence-Based Practice Mahasiswa Program Profesi Ners Stase Keperawatan Medikal Bedah: Studi Dokumen - Fadillah, Jasmine Fasya; Sari, Eka Afrima; Harun, Hasniatisari; Kurniawan, Titis; Nursiswati, Nursiswati (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Evidence-Based Practice (EBP) is one of the important aspects in creating competent nurses. In realizing this, in the nursing education program at the bachelors level, students need to practice in honing the ability to make and report EBP reports. From the results of previous studies, further research is needed that looks at concrete evidence in the form of document studies of EBP work made by students compared to just conducting surveys with questionnaires. So that the institution has a strong foundation in the development of the next EBP curriculum. The purpose of this study is to determine the description of topics and methods of searching for EBP sources chosen during the practice of the undergraduate students in Medical Surgical Nursing unit. This research uses a quantitative descriptive research plan by looking at the overview of the topic and the method of searching for EBP resources used from the results of the document study of the EBP report of PPN students. The sample of this study was 32 EBP reports of nursing professional program students from a nursing education institution in West Java using the total sampling technique. Data analysis on the three variables in this research uses the frequency distribution method which looks at the percentage in each category that exists in each variable. Result Of the 32 EBP reports obtained, it was found that the topic most raised by the undergraduate students in the EBP report based on Problem / Person (P) items was about stroke as many as 6 reports (18.75%). If based on the Intervention item (I), the most raised topic is interventions that can overcome diagnoses related to activity and rest as many as 10 reports (31,25%) and based on the Outcomes (O) item the most raised topic is about the outcome of patient hemodynamic status as many as 6 reports (18.75%). From the study of this document, it was also found that most respondents (62.5%) have used the EBP source search method well. Students' ability to explore the topic of the EBP report and the EBP source search method used is well applied by most students. It is hoped that these results can be a reference for educational institutions regarding the next teaching methods that will be developed related to EBP learning, especially at the KMB station. Keywords: Evidence-Based Practice, Undergraduate Nursing Program, Document Study  ABSTRAK Evidence-Based Practice (EBP) merupakan salah satu aspek penting dalam menciptakan perawat yang kompeten. Dalam mewujudkan hal tersebut, pada program pendidikan keperawatan jenjang profesi Ners, mahasiswa perlu berlatih dalam mengasah kemampuan membuat dan melaporkan laporan EBP. Dari hasil studi terdahulu, diperlukan penelitian lanjutan yang melihat bukti konkrit berupa studi dokumen hasil pengerjaan EBP yang dibuat oleh mahasiswa dibandingkan hanya dengan melakukan survey dengan kuesioner, sehingga institusi memiliki landasan yang kuat dalam pengembangan kurikulum EBP selanjutnya. Tujuan penelitian ini adalah untuk mengetahui gambaran topik dan metode pencarian sumber EBP yang dipilih selama praktik Program Profesi Ners (PPN) stase Keperawatan Medikal Bedah (KMB). Penelitian ini menggunakan rancangan penelitian deskriptif kuantitatif dengan melihat gambaran topik dan metode pencarian sumber EBP yang digunakan dari hasil studi dokumen laporan EBP mahasiswa PPN. Sampel penelitian ini adalah laporan EBP mahasiswa PPN di sebuah institusi pendidikan di Jawa Barat dengan jumlah sampel sebanyak 32 laporan dengan menggunakan teknik total sampling. Analisis data pada ketiga variabel dalam penelitian ini menggunakan metode distribusi frekuensi yang melihat persentase dalam setiap kategori yang ada pada setiap variabel. Dari 32 laporan EBP yang didapatkan, menunjukkan bahwa topik yang paling banyak diangkat oleh mahasiswa PPN dalam laporan EBP berdasarkan item Problem/Person (P) adalah mengenai penyakit stroke sebanyak 6 laporan (18,75%). Jika berdasarkan item Intervention (I), topik yang paling banyak diangkat adalah intervensi yang dapat mengatasi diagnosis terkait aktivitas dan istirahat sebanyak 10 laporan (31,25%) dan berdasarkan item Outcomes (O) topik yang paling banyak diangkat adalah mengenai luaran status hemodinamik pasien sebanyak 6 laporan (18,75%). Dari studi dokumen ini juga didapatkan hasil bahwa sebagian besar responden (62,5%) sudah menggunakan metode pencarian sumber EBP dengan baik.Kemampuan dalam mengeksplorasi topik laporan EBP dan metode pencarian sumber EBP yang digunakan sudah baik diterapkan oleh sebagian besar mahasiswa. Diharapkan hasil tersebut dapat menjadi acuan bagi institusi pendidikan mengenai metode ajar selanjutnya yang akan dikembangkan terkait pembelajaran EBP terutama pada stase KMB. Kata Kunci: Evidence-Based Practice, Program Profesi Ners, Studi Dokumen.